Emission and distribution of ammonia from turkey farm = Emisja i rozprzestrzenianie amoniaku z fermy indyczej - Słobodzian-Ksenicz, Oryna; Jasiewicz, Marzena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of the study was to determine the emissions of ammonia and the extent of its impact on the environment. On the farm there are two livestock buildings. The ammonia emission was calculated on the basis of the emission ratio per 1 m2of the usable area of the building, for females determined at 1.38 kg per annum.
Keywords: ferma indycza; emisja amoniaku; zakres oddziaływania amoniaku; turkey farm; ammonia emission; extent of the impact of ammonia